ChemInform Abstract: Insight into the Regioselectivity of Nucleophilic Ring‐Opening of Azetidinium Ions Containing Quaternary Carbon Atoms. Issue 14 (20th March 2013) - Drouillat, Bruno; Wright, Karen; David, Olivier; Couty, Francois
Abstract Title compounds are treated with three different nucleophiles.